A participatory sustainable rangeland management toolkit with a holistic and multidisciplinary approach - Louhaichi, Mounir (PANORAMA - Solutions for a Healthy Planet, 2023)
Panorama solutions on Sustainable Rangeland Management (SRM) toolkit which is tested in North Africa and West Asia (NAWA region), with a specific focus on Tunisia, Jordan and Uzbekistan, and offers a package of holistic and multi-disciplinary tools for addressing the root cause of rangeland degradation. The toolkit will help communities, policy and development actors use key sustainable rangeland management practices at local scale or in context-specific environments expecting to ensure that ecosystem services are used sustainably and reach a level of land degradation neutrality, increase livestock feed (forage) production, enhance ecosystem services.